Karakalpak Calendar - Mythological Legends - Kalbaeva Gulparshin Sarsenbaevna (Researchparks Publishing, 2021)
The article deals with genre peculiarities, ideological-thematic direction of calendar – mythological legends. It also reveals the historical bases of creation of such types of legends. Historical principles of these legends are revealed on the base of rich folk materials in connection with notions (ideas) of the people of primitive society including cults of nature, origin of time accounting, as well as with mythological ideas, popular superstitions (beliefs) and spiritual values of Iranian and Turkic peoples. The object of the research are legends, widespread among Turkic peoples of Central Asia, myths and legends of Iranians about origin of time accounting, information adduced in ancient written records as well. In the article comparative historical, historical-genetic and structural-typological methods are used.